THE EFFECT OF BALL MILLING ON THE MORPHOLOGY OF CUBIC BORON NITRIDE - Aarudi, Shashikala A.R,; Kothakula, Keerthi; C S, Ramesh; B S, Sridhar (Malaysian Journal of Science, 2023)
Due to its attractive properties, cubic boron nitride (c-BN) finds extensive applications in mechanical and electronic industries. The conversion of micro c-BN to nano c-BN remarkably influences the properties. This study investigates the effect of ball milling on the morphological parameters. Boron nitride was subjected to different hours of ball milling process at different rotation speeds. The crystallite size of the c-BN was measured at different ball milling time intervals, and we observed that after 100 hours, the crystallite size decreased to nano size. The ball milling was increased to 150-175 hours to get less than 100 nm size particles. The surface morphology and elemental analysis of the samples were done using SEM and EDX studies. EDX confirmed the presence of boron and nitrogen in the sample. SEM images indicated that the agglomerated morphology of c-BN particles had an irregular shape. The cubic structure was confirmed from XRD studies. Thermogravimetric analysis (TGA) conducted to determine the samples' thermal stability indicated that weight loss was observed for temperatures up to 700oC. There was no significant weight loss at a higher temperature. Stronger reflectance was observed with increased ball milling time in UV-Visible DSR studies.